The Hospital of Tomorrow Case Study: Multidisciplinarity, Inclusiveness and Holistic Approaches to Foster Innovation in Complex Organizations - Francesca Gorla; Anja Borojevic; Chiara Gibertoni; Lorena Landi; Marco Storchi; Luca Fontana; Jetri Regmi; Barbara Burmen; Anna Silenzi (Kerman University of Medical Sciences, 2023)
Background  This case study describes and analyses an action research initiative undertaken by management, staff and World Health Organization (WHO) at the IRCCS Azienda Ospedaliero-Universitaria di Bologna, Policlinico di Sant'Orsola, Italy. The initiative utilised staff engagement approaches developed during the COVID-19 pandemic to rethink and reshape future development plans. The initiative provides a 'how-to' case study for complex health facilities on ways to create similar multisectoral, inclusive and holistic processes in planning structural, functional and organizational solutions for their 'hospitals of tomorrow.'Methods  The case study utilised an action research approach coordinated by a team of WHO facilitators in close collaboration with the Board of Hospital Directors. Heterogeneous and multidisciplinary working groups were created, with members from different levels of the hospital staff. In the context of facilitated group meetings held weekly over a one-year period, participants were asked to review topics of interest to future plans of the hospital and make recommendations on effective/innovative ways of addressing these in the short and long term. Working groups focused on different challenges.Results  The initiative was successful in creating and sustaining broad staff engagement in the future planning processes. 80% groups maintained high staff participation throughout the entire project year. Participating staff reported enhanced communication and cooperation between departments represented in different groups. 87% of the proposed plans suggested by the working groups were approved by the Board for implementation.Conclusion  Key factors contributing to the high approval rate of plans, strong engagement record of staff and enhanced cooperation between involved departments; included: multisectoral/cross hierarchal staff involvement, group attention to defining time-bound contextual goals, flexible implementation monitoring approaches, personnel skills and profiles of participants, direct and open communication at all levels and times, member commitment and clear exit strategy. The case study is presented as a model to stimulate similar actions in other complex healthcare facilities.